2019
DOI: 10.15171/apb.2019.056
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effects of PI3K/Akt Signaling Inhibition on PTEN and P53 in Prevention of Acute Lymphoblastic Leukemia Tumor Cells

Abstract: Purpose: The PI3K/Akt signaling pathway regulates cell growth, proliferation and viability in hematopoietic cells. This pathway always dysregulates in acute lymphoblastic leukemia (ALL). PTEN and P53 are tumor suppressor genes correlated with PI3K/Akt signaling pathway, and both have a tight link in regulation of cell proliferation and cell death. In this study, we investigated the effects of dual targeting of PI3K/Akt pathway by combined inhibition with nvp-BKM-120 (PI3K inhibitor) and MK-2206 (Akt inhibitor)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 64 publications
1
23
1
1
Order By: Relevance
“…Matching our data Simioni et al detected decreased AKT phosphorylation in SEM cells incubated with 0.5 µM MK-2206 for 30 min [ 15 ]. Han et al obtained similar results in NALM-6 cells [ 16 ] and Naderali et al observed AKT dephosphorylation in NALM-6 and REH cells [ 17 ]. However, both studies only surveyed one particular time point using a single concentration of MK-2206.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Matching our data Simioni et al detected decreased AKT phosphorylation in SEM cells incubated with 0.5 µM MK-2206 for 30 min [ 15 ]. Han et al obtained similar results in NALM-6 cells [ 16 ] and Naderali et al observed AKT dephosphorylation in NALM-6 and REH cells [ 17 ]. However, both studies only surveyed one particular time point using a single concentration of MK-2206.…”
Section: Discussionmentioning
confidence: 64%
“…However, due to its high oncogenic potential and frequent dysregulation it remains a key target for pharmacological intervention. Regarding B-ALL only few groups investigated the effect of sole AKT inhibitors: Levy et al demonstrated that GSK690693 acted anti-proliferative and induced apoptosis [ 13 , 14 ] while three other manuscripts investigated pan-AKT inhibitor MK-2206 [ 15 , 16 , 17 ]. Both drugs induced significant anti-proliferative effects in leukemic cell lines and changes in AKT downstream protein phosphorylation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that PI3K/Akt promotes p53 translation in cancer development (63). Inhibition of PI3K/Akt signaling leads to p53 upregulation in leukemic cancer cells (64). A recent study has reported p53 upregulation due to PI3K/Akt signaling inhibition in EMT inhibition in liver cancer cells (65).…”
Section: Discussionmentioning
confidence: 98%
“…On the contrary, the LoF of AKT prevails on the GoF of PI3K as their combination increases p53 concentration. This could be due to the relationship between PI3K and AKT since PI3K activation is upstream to the AKT signal (Naderali et al, 2019) . Therefore, AKT reduction plays a predominant role on p53 levels regardless of PI3K activation.…”
Section: Gof Of Pi3k K-ras and Raf And Lof Of Pten And Akt Determinmentioning
confidence: 99%